Partial Edentulism in Patients Visiting the Dental Out-Patient Department at the Tertiary Care Centre in the Eastern Part of Nepal - Shrestha, Pragya; Bhagat, T. (Journal of Nepalese Prosthodontic Society, 2018)
Introduction: Partial edentulism is an irreversible condition resulting from various dental diseases like dental caries and periodontal lesions. Loss of teeth produces deleterious effects on masticatory function, phonetics, facial appearance and comfort of the patients. If not restored on time, it can lead to pathological changes in vertical dimension, occlusion and temporomandibular joint. Methods: This study was conducted in the department of Prosthodontics, CODS, BPKIHS from September 2015 to March 2016. All patients above the age of 14 years presenting with partial loss of dentition and willing to give informed consent were included in the study. Data regarding age, gender, missing teeth, cause of permanent tooth loss and age of first permanent tooth loss were collected from 750 patients. Results: Dental caries was the major cause of tooth loss accounting for 60.5% of the study population followed by periodontal disease (14.0%) and trauma (11.9%). First permanent tooth loss was highest in the age group of 35-44 years (22.9%). The most common type of partial edentulism was found to be Kennedy’s class III followed by class IV, class I and class II in both the arches. Conclusions: The most common cause of permanent tooth loss was dental caries in the study population. The first permanent tooth loss was found to be highest in age group 35-44 years. The most common type of partial edentulism was the Kennedy’s class III in both the arches.